2010
DOI: 10.1093/jjco/hyq205
|View full text |Cite
|
Sign up to set email alerts
|

High Jagged1 Expression Predicts Poor Outcome in Clear Cell Renal Cell Carcinoma

Abstract: Notch signaling may play an important role in the progress of renal cell carcinoma. Jagged1 expression may be useful for predicting prognosis in patients with renal cell carcinoma, especially at the early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
6
28
0
Order By: Relevance
“…Our previous study demonstrated Notch1 activation can promote RCC growth via PI3K/Akt signaling, 12 and we also found that the expression level of Jagged1, a Notch ligand, was an independent predictor of poor survival in patients with ccRCC. 28 In accordance with these studies, we showed ICN1 expression was positively correlated with tumor size and Fuhrman grade, which implied that ICN1 might be related to progression of ccRCC. We also found a significant correlation between ICN1 expression and tumor necrosis, which might be due to rapid tumor growth mediated by ICN1 upregulation.…”
Section: Commentsupporting
confidence: 85%
“…Our previous study demonstrated Notch1 activation can promote RCC growth via PI3K/Akt signaling, 12 and we also found that the expression level of Jagged1, a Notch ligand, was an independent predictor of poor survival in patients with ccRCC. 28 In accordance with these studies, we showed ICN1 expression was positively correlated with tumor size and Fuhrman grade, which implied that ICN1 might be related to progression of ccRCC. We also found a significant correlation between ICN1 expression and tumor necrosis, which might be due to rapid tumor growth mediated by ICN1 upregulation.…”
Section: Commentsupporting
confidence: 85%
“…The NOTCH pathway has been shown to be an oncogenic pathway in T cell acute lymphoblastic leukemia and head and neck cancers (16 -18), and activating NOTCH mutations have been shown to occur in some of these tumors. Components of the NOTCH signaling pathway have been shown to be active in RCC also (10,19,20), although not many NOTCH mutations have been seen in these tumors. Furthermore, even though mutations have been described in the NOTCH receptors in some tumor samples, they are not sufficient to explain the activation of this pathway in the majority of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was demonstrated that in spheroids, all genes in Notch signaling are significantly upregulated, particularly Jagged1 , DLL3 and Notch1 . High Jagged1 expression has been demonstrated to predict a worse outcome in breast cancer (35,36), renal cell carcinoma (37) and colon adenocarcinoma (38). It has also been reported that high Jagged1 expression is associated with prostate cancer recurrence (39).…”
Section: Discussionmentioning
confidence: 99%